School milk scheme: through the perspective of legislation / Norfarahiyah Abdul Halim and Liana Zir Mohd Uzir - Abdul Halim, Norfarahiyah; Mohd Uzir, Liana Zir (2008)
The School Milk Scheme is one of the Ministry of Education programs under the Food Supplementary Program. This scheme had established for more then 30 years to help distributing free milk to the poor and under privileges students in primary school. However this scheme has been suspended in August 2007 due to the food poisoning cases cause by the School Milk. Under this School Milk Scheme, government had referred to the Food Act 1983(Act 281) & Food Regulation 1985, Consumer Protection Act 1999(599) & Regulation and also the Guideline known as Garis Panduan Pengendalian Bekalan Susu Sekolah to supervise this scheme. However there are still weaknesses occurred under this scheme such as no proper rules and regulation that specifically on the subject of School Milk, no proper guideline in terms of handling, distributing and packaging the School Milk and the Ministry of Healthy still using the traditional method to discover organism and bacteria in the Milk. Through this research we have suggest and recommend several solution to help the government to solve the problem of food poisoning cause by the School Milk. Among the way of solutions are by upgrading and improving the Guideline on handling, packaging and distributing the School Milk, upgrading the procedure of testing method to discover the bacteria and organism inside the milk and implement and improvement the present and existing laws that already have in our country. We hope by doing this research it can assist to reduce the problem that relating the food poisoning cause by School Milk.